Peramalan Indeks Harga Properti Residensial di Kota Yogyakarta Tahun 2024 - Hasan, Ahmad Dhitsah (Indo-Fintech Intellectuals: Journal of Economics and Business, 2024)
This study aims to forecast the demand for residential property in Yogyakarta for the period of Q1 to Q4 2024. The ARIMA (Autoregressive Integrated Moving Average) model is used to analyze historical data and determine the best model for each type of IHPR (Residential Property Price Index): simple, middle, and luxury. The results of the study show that the ARIMA (0,1,1) model is selected for simple IHPR, ARIMA (1,1,1) for middle IHPR, and ARIMA (1,1,0) for luxury IHPR. The forecasting results show a positive trend for all types of IHPR, indicating the growth of the residential property sector in Yogyakarta in the forecasted period. However, there is insignificance in the ARIMA (0,1,1) model for simple IHPR, so further research is needed to verify the forecasting results. Overall, this study provides an optimistic picture of the prospects for the residential property sector in Yogyakarta for the period of Q1 to Q4 2024. This information can help stakeholders make strategic decisions in the property industry